Economic Performance Evaluation of Tourism in Pearl River Delta Based on AHP Model. (4th May 2022) - Huang, Qiuxia; Zhang, Wenliang
Abstract : With the development of the times, the leading role of tourism in economic growth has become increasingly prominent. Tourism economic performance is an important standard to measure the development of its economy. However, there is no quantitative research on tourism economic performance within a single region. Therefore, on the basis of relevant research, this paper first constructs the tourism economic performance evaluation system from four aspects such as industrial scale, economic benefits, support power, and input and output. Then, based on the relevant data of tourism indicators in the Pearl River Delta in the past five years, the analytic hierarchy process was introduced to evaluate the economic performance of tourism in the Pearl River Delta. The results show that the tourism industry in the Pearl River Delta has good economic benefits and large industrial scale. However, the social motivation and input-output efficiency supporting the development of tourism are poor. Finally, according to the evaluation results, we put forward the methods and suggestions of tourism efficiency optimization in the Pearl River Delta region, so as to further promote the development of tourism in the Pearl River Delta region.